Pelatihan Analisis Usaha, Penerapan Teknologi, Dan Digital Marketing Pada Usaha Mikro Pempek - Whetyningtyas, Aprilia; Faidah, Faridhatun; Nadia, Linda Putri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Entrepreneurial development can improve the community's economy by opening new jobs and helping increase economic growth. Business actors must be adaptive to technology to increase their turnover. The partner of this service activity is the Pempek micro business